The Influence Of Local Taxes And Local Retributions On Regional Expenditure Through Local Own-Source Revenue As A Mediating Variable During The Pandemic Period(Empirical Study In Cities/Districts In West Java) - Ervina, Ervina; Hidayah, Nurul (Devotion : Journal of Research and Community Service, 2024)
Local Own Source Revenue had been greatly impacted by the Covid-19 pandemic. Local Taxes and Local Retribution has been decreased as many hotels, restaurants and entertainment businesses were not allowed to open. The aim of this research is to determine the effect of Local Taxes and Local Retribution during the Covid-19 pandemic on Local Own Source Revenue, which impacted on Capital Expenditures during the Covid-19 pandemic. The population in this study is 54 Local Government Yearly Financial Statement from 27 cities/regencies in West Java Province for 2020 and 2021. Sampling Method that is being used is non probability sampling method, with a total sample of 54. The independent variables of this research are Local Taxes and Local Retributions, the dependent variable of the research is Capital Expenditure and the mediation variable is Local Own Source Revenue. The research results show that Local Taxes and Local Retribution have a significant positive effect on Local Own Source Revenue and Capital Expenditures during the Covid-19 pandemic, and Local Own Source Revenue positively mediates Local Taxes and Local Retriburtion on Capital Expenditures during the Covid-19 pandemic.